THE EFFECT OF ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) AND CAPITAL STRUCTURE ON FIRM VALUE: THE ROLE OF FIRM SIZE AS A MODERATING VARIABLE - Wulandari, Priska; Istiqomah, Dyah Febriantina (Jurnal Riset Akuntansi Politala, 2024)
This research aims to examine the effect of Environmental, Social, and Governance (ESG) and capital structure on firm value moderated by firm size variables. Good ESG disclosure will attract investors to invest in a company so that it can increase the value of the company. The research sample of 47 mining companies listed on the Indonesia Stock Exchange was taken using a purposive sampling technique. The research observation period was 2021-2022, so the total observations were 94 subjects. This research uses a quantitative approach. The data collection method is documentation through secondary data collection on annual financial reports and sustainability reports, the data analysis technique is moderated regression analysis (MRA) using Eviews Enterprise 12 software. The results showed that ESG has no positive effect on firm value, but capital structure and firm size have a negative effect on firm value. Firm size is unable to moderate the effect of ESG on firm value but can moderate the effect of capital structure on firm value.